Synthesis and Characterization of Poly(Amidoamine) Dendrimers Encapsulated 198Au Nanoparticles - R. Ritawidya; A. Pujiyanto; Mujinah Mujinah; Witarti Witarti; Setiawan Setiawan; M. Ramli; D. Kurniasih; A. Yanuar; A. Mutalib; L.B. Kardono (PPIKSN-BATAN, 2012)
Brachytherapy or internal radiotherapy is one of many methods used for treatment of cancer. This modality requires an agent with radionuclides that emits α or β particle with a proper energy. 198Au (99% β max = 0.96 MeV and t1/2 = 2.69 days) is one of radionuclides that has been considered to be effective for the above-mentioned purpose. The purpose of this research was to synthesis and characterize poly(amidoamine) (PAMAM) G3.0 dendrimers encapsulated 198Au nanoparticles as a new brachytherapy agent. PAMAM G3.0 dendrimers encapsulated 198Au nanoparticles was successfully synthesized by a bottom-up method using sodium borohydride as a reductor. Purification was then performed by a size exclusion chromatography in order to separate large Au nanoparticles that were formed outside the cavity of PAMAM G3.0 dendrimers. Prior to the synthesis of PAMAM G3.0 dendrimers encapsulated 198Au nanoparticles, the synthetic procedure was first established by using a non-radioactive Au. The PAMAM G3.0 dendrimers encapsulated Au nanoparticles produced was then characterized by using an UV-Vis spectroscopy, a transmission electron microscopy (TEM), particle size analyzer (PSA), and an atomic absorption spectroscopy (AAS). Characterization results revealed that PAMAM G3.0 dendrimers encapsulated Au nanoparticles that were prepared from a reaction mixture of PAMAM G3.0 dendrimers and Au HAuCl4 with mol ratio of 2.8, was found to be a proper formula. It produced PAMAM G3.0 dendrimers encapsulated Au nanoparticles with diameter of 1.743 nm, spheris, uniform and drug loading value of 26.34%. This formula was then used in synthesis using radioactive Au, 198Au. Characterization results of PAMAM G3.0 dendrimers encapsulated 198Au nanoparticles gave a radiochemical purity of 99.4% and zero charge. Received: 04 December 2012; Revised: 18 December 2012; Accepted: 20 December 2012